Audit And Evaluation Of CBT Examination System At SMK Muhammadiyah-10 Kisaran Using Cobit 2019 Framework - Zulfan; Khairul; Andysah Putera Utama Siahaan (Jurnal Sistem Komputer dan Informatika (JSON), 2026)
This study aims to audit and evaluate the Computer Based Test (CBT) system for Academic Ability Tests (TKA) at SMK Muhammadiyah 10 Kisaran using the COBIT 2019 framework through a mixed-methods descriptive approach with data collection techniques including observation, semi-structured interviews, questionnaires based on COBIT 2019 capability indicators, and documentation studies, focusing on five COBIT 2019 domains: EDM03 (Ensure Risk Optimization), APO12 (Manage Risk), APO13 (Manage Security), DSS01 (Manage Operations), and DSS05 (Manage Security Services), with 8 respondents consisting of the principal, curriculum vice principal, IT team, proctors, technicians, and teachers determined through purposive sampling based on RACI chart analysis. The results show that the overall capability level of CBT system governance is at Level 2 (Managed Process) with an average score of 2.22, while DSS01 reaches Level 3 (Established Process) with a score of 3.01, and the gap analysis reveals significant discrepancies between actual conditions and the expected Level 4 (Predictable Process), with EDM03 having the largest gap (2.08) and only 48% achievement, identifying EDM03, APO12, APO13, and DSS05 as priority domains requiring immediate improvement due to their high impact on TKA implementation reliability and security. This research contributes a comprehensive evaluation model integrating risk analysis, IT-Related Goals, and COBIT 2019 capability levels for CBT systems in vocational high schools, which is still rarely studied in the Indonesian educational context, providing both theoretical contributions to the development of information system audit studies in education and practical benefits as evaluation material and a basis for CBT system improvement for school management.